Diagnostic yield of scope retroflexion in the right colon: A prospective cohort study. Issue 2 (February 2016) - Triantafyllou, Konstantinos; Tziatzios, Georgios; Sioulas, Athanasios D.; Beintaris, Iosif; Gouloumi, Alina-Roxani; Panayiotides, Ioannis G.; Dimitriadis, George D.
Abstract: Background: Techniques have been implemented to improve colonoscopy adenoma detection rate (ADR) in the right colon. Aims & methods: We prospectively examined the additional diagnostic yield of right colon examination with colonoscope retroflexion in consecutive, symptomatic and screening–surveillance patients. Right colon was examined in forward-view first and thereafter, retroflexion was performed to re-inspect it. Results: Right colon examination in retroflexion was achieved in 620 (92%) patients. Increased inserted scope length to the cecum (OR: 0.48 [95%CI: 0.27–0.84]) and elderly status (OR: 0.53 [95%CI: 0.430–0.94]) predicted retrofexion failure. Forward-view colonoscopy detected 134 polyps and 112 adenomas in 105 and 85 patients, respectively. Scope retroflexion revealed 7 missed (6 adenomas – 2 advanced) polyps in 7 patients; indicating 4.96 (95%CI: 1.37–8.55)% and 5.1 (95%CI: 1.12–9.05)% per-polyp and per-adenoma miss rates, respectively. In ITT analysis, per-patient polyp and adenoma miss rates were 1.041% and 0.89%, respectively. Among screening–surveillance patients, retroflexion detected 3 missed adenomas (2 advanced) in 3 patients, resulting in changed surveillance schedule in 2 of them (5.12 per 1000 screening–surveillance patients). Early study termination was favored by low right colon ADR improvement and lacking substantial surveillance interval change. Conclusion: The additional diagnostic yield of scope retroflexion in the right colon is questionable.